2010
DOI: 10.1016/j.molcel.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

SRC-3Δ4 Mediates the Interaction of EGFR with FAK to Promote Cell Migration

Abstract: Summary EGF induces signal transduction between EGFR and FAK, and FAK is required for EGF-induced cell migration. It is unknown, however, what factor mediates the interaction between EGFR and FAK and leads to EGF-induced FAK phosphorylation. Here we identify SRC-3Δ4, a splicing isoform of the SRC-3 oncogene, as a signaling adaptor that links EGFR and FAK and promotes EGF-induced phosphorylations of FAK and c-Src. We identify three PAK1-mediated phosphorylations in SRC-3Δ4 that promote the localization of SRC-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 36 publications
3
119
0
Order By: Relevance
“…FAK Tyr194 phosphorylation by c-Met appears to interfere with the inhibitory intramolecular interaction leading to its activation (Chen et al, 2011). The FAK FERM domain also binds EGF receptor, promoting migration via mediation of the intermediary protein SRC3D4 after EGF treatment (Long et al, 2010). These previous studies support growth factor (but not adhesion) -mediated FAK activation though interactions of the FERM domain and growth factor receptors.…”
Section: Discussionmentioning
confidence: 68%
“…FAK Tyr194 phosphorylation by c-Met appears to interfere with the inhibitory intramolecular interaction leading to its activation (Chen et al, 2011). The FAK FERM domain also binds EGF receptor, promoting migration via mediation of the intermediary protein SRC3D4 after EGF treatment (Long et al, 2010). These previous studies support growth factor (but not adhesion) -mediated FAK activation though interactions of the FERM domain and growth factor receptors.…”
Section: Discussionmentioning
confidence: 68%
“…This increase in transcription is most likely due to a relief of repression of the endogenous AIB1 in the COS-7 cells because we are able to detect endogenous AIB1 protein by Western blot (17). Previous studies from our group and others have suggested that the N-terminal region containing the bHLH and PAS A domains contains an inhibitory domain that represses activity in both the nucleus and cytoplasm (17,18,21,26,36). Our studies and those from Chen et al (36) have shown that the loss of the N-terminal region leads to potent coactivation of nuclear hormone receptor-mediated transcription.…”
Section: Discussionmentioning
confidence: 74%
“…These data suggest a suppressor role of the N-terminal region of AIB1 in the regulation of the coactivator function of AIB1. This region is the most highly conserved region among steroid receptor coactivator proteins and has been suggested to contain an inhibitory function for AIB1 also in the cytoplasm (21).…”
Section: Journal Of Biological Chemistry 26821mentioning
confidence: 99%
“…4C). c-Src is a tyrosine kinase which is involved in the phosphorylation and activation of FAK [35]. By means of western blotting analysis we demonstrated that in MDA-MB231 cells SAHA and TRAIL neither alone nor in combination modified the level of c-Src (not shown).…”
Section: The Effects Of Saha and Trail On The Level Of Integrins And Fakmentioning
confidence: 89%